Concurrent and Delayed Behavioral and Monoamine Alterations by Excessive Sucrose Intake in Juvenile Mice - Choe, Won-Hui; Lee, Kyung-A; Goto, Yukiori; Lee, Young-A (Frontiers in Neuroscience, 2020)
Our daily diet in the modern society has substantially changed from that in the ancient past. Consequently, new disorders associated with such dietary changes have emerged. For instance, excessive intake of compounds, such as sucrose (SUC), has recently been reported to induce pathological neuronal changes in adults, such as food addiction. It is still largely unclear whether and how excessive intake of such nutrients affects neurodevelopment. We investigated changes in behavior and monoamine signaling caused by excessive, semi-chronic intake of SUC and the non-caloric sweetener saccharin (SAC) in juvenile mice, using a battery of behavioral tests and high-performance liquid chromatography. Both SUC and SAC intake induced behavioral alterations such as altered amphetamine responses, sucrose preference, stress response, and anxiety, but did not affect social behavior and cognitive function such as attention in juvenile and adult mice. Moreover, SUC and SAC also altered dopamine and serotonin transmission in mesocorticolimbic regions. Some of these behavioral and neural alterations were triggered by SAC and SUC but others were distinct between the treatments. Moreover, alterations induced in juvenile mice were also different from those observed in adult mice. These results suggest that excessive SUC and SAC intake during the juvenile period may cause concurrent and delayed behavioral and monoamine signaling alterations in juvenile and adult mice, respectively.